Learning French in a Late Thirteenth-Century English Bakehouse - Sayers, William (Petits Propos Culinaires, 2009)
This essay studies the the vocabulary of milling and baking found in the Anglo-Norman didactic treatise/ poem by Walter of Bibbesworth , an educational text for gentry families seeking instruction in the French language which came equipped with English glosses.